Effectiveness of An Instructional Program on Pulmonary Tuberculosis Patients Quality of Life Concerning General Health-Related among sample in Baghdad City - ali, abdulkhaliq; Atiyah, Rabab (Iraqi National Journal of Nursing Specialties, 2017)
Objective(s): This research aims at evaluating the quality of pulmonary tuberculosis patients life before and after applying the suggested instructional program, and to find out relationships among distribution of an overall assessment quality of life improvement and socio-demographic characteristics variables. Methodology: Self controlled design studying effectiveness of applying instructional program on quality of life for pulmonary tuberculosis patients among sample size (65) patients from primary health care centers/AL-Sadur City sector-the consultation clinic of chest and respiratory diseases at AL-Rusafa health directorate, and Ibn-Zuhr Hospital at Baghdad city. An instructional program has been applied with an approach of pre-test and post-test for checking improvements on the study sample concerning quality of life. This study applied format of General World Health Organization Quality of Life-BERF Questionnaire.The methods used descriptive statistics (Observed frequencies, percentages, mean of score, standard deviation, relative sufficiency, and Stem–Leaf plot method) to evaluate the General QoL-Improvements, as well as inferential statistical methods are used such that (Wilcoxon Signed Rank, McNemar, and Analysis of covariance (ANCOVA)). Results: Results shows that studied disease is classified to indigence diseases, as well as results shows effective of smoking cigarette/or any other types especially for those who had smoking long duration more than 10 years. Results indicated that there has been a highly significant differences at P<0.01 among different responding complain items, and increases patients who had suffered from: "chest pain, difficult breathing / dyspnea, anorexia, weight loss, general weakness, and especially when answering: Is there any infected member in your family?", which have cleared the effectiveness of diseases communication . Suggested of instructional program shows a highly stating of improvements with pulmonary tuberculosis patients and results illustrated that most of questionnaire’s items are assigned meaningful improvements significantly at P-values <0.05, as well as weak relationships are accounted between General QoL improvements and Socio-demographical Characteristics variables, with no significant relationships at P-values >0.05. Recommendations: Application the suggested instructional program in all consultation clinic for chest and respiratory disease and its coordinator tuberculosis units after training specialized staff, for patients who attending the centers monthly, Invite previous patient who was suffered from the disease to attendance the lectures and to participate with his own experiment about the impact of the disease on quality of life and shared differing viewpoints, in open discussion circles. Governmental commitment by offering all support to the National Tuberculosis Program generally and to TB patients especially, by enhancing their socio-economic state by providing financial donation.